Lower facial remodeling with botulinum toxin type A for the treatment of masseter hypertrophy - Fernanda Homem de Mello de Souza Klein; Fabiane Mulinari Brenner; Maurício Shigeru Sato; Fernanda Manfron Batista Rosas Robert; Karin Adriane Helmer (Sociedade Brasileira de Dermatologia, 2014)
BACKGROUND: Masseter hypertrophy has been treated with botulinum toxin injections because of esthetic complaints especially in Asians. OBJECTIVES: The goal of the present study was to evaluate the efficacy of abobotulin toxin use in masseter hipertrophy treatment in Brazilians. METHODS: Ten Brazilian female patients with masseter hypertrophy were subjected to injections of 90U of abobotulinum toxin A applied on each side respecting the safety zone stabilished in literature and were followed up for 24 weeks. RESULTS: When analyzing the coefficients between measures of middle and lower third of the face obtained from standardized photographs, an increase was observed, with statistical significance at 2 weeks (p=0.005) and 12 weeks (p=0.001). The progression of lower third reduction was 3.94%, 5.26%, 11.99%, and 5.47% (2, 4, 12, and 24 weeks respectively). All patients showed improvement in bruxism after treatment. Observed adverse effects were masticatory fatigue, smile limitation, and smile asymmetry. CONCLUSION: The use of abobotulinum toxin A for masseter hypertrophy is effective in Brazilians and reached its maximum effect of facial thinning at 12 weeks. Smile limitation had a higher incidence compared to that reported in the literature and may result from risorius muscle blockage caused by toxin dissemination. Despite its side effects, 80% of the patients would like to repeat the treatment.